Ubiquity of Neoplasms in Canines of Mumbai Region - Gunjate, Babasaheb B.; Kadam, Dattatray P.; Khandekar, Gajender S.; Dalvi, Santosh H.; Khandekar, Gaurav G.; Saini, Dishant (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Neoplasia is common in pet dogs, but the literature documented on its incidence is sparse. The purpose of this study was to document the occurrence of tumours in a defined population of Mumbai and their nearby regions. Fifty cases of canine confirmed neoplasm were considered in this research database. The tissue samples were collected on surgery and processed for the histopathological examination and were classified accordingly. During the collection of tissue samples, the age, sex and breed of the respective canines were also recorded. The occurrence of adenocarcinoma was highest (26%) and majority of affected canines were female. The Mongrel (non-descript) dogs were most commonly affected with a prevalence of 52% and the average age of dogs having tumour was 7.00 years.